Persepsi Guru Terhadap Perkembangan Akademik Secara Berkelanjutan - Audia Amanda Tarigan; Azra Humaira; Evy Juliani Siregar; Fatimah Azzahra Lubis; Muhammad Farhan Khairuman (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to see how sustainable teacher academic development is. This type of research is a type of qualitative research. There are various ways to improve teacher competency, one of which is through the PKB program. In this regard, it is hoped that the four teacher competencies which include pedagogical, professional, social and personality competencies can be improved so that teachers' desires and demands can be achieved optimally in accordance with their profession. If the teacher's performance assessment is still low according to competency standard criteria, then the teacher is obliged to carry out PKB that focuses on achieving teacher competency standards. A strategic step in sustainable professional development is through the Teacher Working Group forum. This KKG Forum is a forum for formulating Sustainable Professional Development programs. The preparation of the PKB program is carried out through regular meetings of teachers, supervisors and school principals to discuss the programs needed by teachers, especially PKB.